Formation of volatile compounds in salt-mediated naturally fermented cassava - Alberta N.A. Aryee; Christabel Tachie; Aleksei Kaleda (Food Chemistry: X)
Cassava is a starchy staple typically consumed in tropical countries; however, its high moisture content renders it susceptible to post-harvest deterioration. Fermentation has been used to improve shelf-life, functional properties, nutrient bioavailability, minimize toxic compounds, and alter aroma. In this study, the effect of added salt (5–25 %) on the pH, titratable acidity (TTA), and volatile compounds (VOCs) in cassava fermented was investigated. A sharp reduction in pH from 6.98 to 6.20 to 4.81–4.00 and concomitant increase in TTA (0.027–0.297 %) was observed in all the samples on day 2 except the 25 % added salt ferments. The 32 VOCs quantitated on day 50 by headspace solid-phase microextraction (HS-SPME) arrow coupled with gas chromatography–mass spectrometry (GC–MS) and classified as: alcohol (9), aldehydes (6), ketones (5), carboxylic acids (5), esters (3), nitriles (2), phenol (1) and hydrocarbon (1) were affected by the amount of added salt. PCA explained 68.50 % of the variance and cluster samples based on the similarities between the identified VOCs and showed that fermentation mediated by 15 % added salt presented a VOCs profile comparable to using 20 % of salt, with the former representing a lower cost. The addition of salt can be used to control acidification, adopted as an effective preservation technique, and mediate VOCs production during cassava fermentation.